1991
DOI: 10.1007/bf01800477
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of molybdenum cofactor deficiency by assay of sulphite oxidase activity in chorionic villus samples

Abstract: Molybdenum cofactor deficiency is characterized by the absence of sulphite oxidase, xanthine dehydrogenase and aldehyde oxidase, the three known enzymes in man that require the cofactor for their activity. Prenatal diagnosis of the deficiency may be performed by assay of sulphite oxidase activity in cultured amniocytes. However, the activity in amniocytes is low and large numbers of cells are required for reliable assessment. We show that sulphite oxidase is present at high levels in chorionic villi obtained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Prenatal diagnosis may be carried out by assay of sulphite oxidase activity or DNA mutation analysis on uncultured chorionic villus samples collected at 11-14 weeks gestation. The use of DNA analysis is only possible if the index case has been previously characterised by those means [6,7]. These techniques avoid the delays inherent in enzyme analysis on cultured amniocytes, a method that has also been used in this condition [9].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis may be carried out by assay of sulphite oxidase activity or DNA mutation analysis on uncultured chorionic villus samples collected at 11-14 weeks gestation. The use of DNA analysis is only possible if the index case has been previously characterised by those means [6,7]. These techniques avoid the delays inherent in enzyme analysis on cultured amniocytes, a method that has also been used in this condition [9].…”
Section: Discussionmentioning
confidence: 99%
“…13.5 mg of uncultured chorionic villi were tested for sulphite oxidase activity by the method of Johnson et al (1991). Our mean value of 55 controls is 40 15 ukat/kg prot.…”
Section: Measurement Of Enzyme Activities and Mutation Detectionmentioning
confidence: 99%
“…The complete Mo-co appears in four basic configurations, whose structures have been determined by a combination of rigorous biochemical studies and confirmed by the emergence of a large amount of structural data (Johnson and Rajagopalan 1982;Johnson et al 1990Johnson et al , 1991Hilton and Rajagopalan 1996;Solomon et al 1997). The cofactor typically has a tricyclic pyranopterin structure, with pyrimidine, pyrazine, and pyran rings, respectively.…”
Section: Further Biochemical Modificationsmentioning
confidence: 98%
“…Also attached to this ring is a phosphomethyl group, and it is the presence of a terminal phosphate that has led to this form of the cofactor being referred to as a mononucleotide. Given the dominance of the pyranopterin structure (tricyclic) over the original molybdopterin (bicyclic) structure developed on the basis of chemical studies (Johnson and Rajagopalan 1982;Johnson et al 1990Johnson et al , 1991, it is referred to as Mo-PPT or W-PPT when complexed with Mo or W, respectively. Mo-PPT is the form of the cofactor found in eukaryotes and in essentially all sulfite oxidase enzymes (SUOX) and some xanthine dehydrogenase enzymes (XDH).…”
Section: Further Biochemical Modificationsmentioning
confidence: 99%